PENGARUH METODE PRIVAT TERHADAP KELANCARAN MEMBACA IQRA’ DI MADRASAH DINIYAH TPA/TPQ “HIDAYATUSH SHIBYAN” NGRECO KABUPATEN KEDIRI - Itsna Rusydiana; Amalia Majid, Fitri; Mar’atus Sholihah, Binti; Soleh, Ibnu; Nur Azizah, Ulfa (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2022)
This research aims to evaluate the effectiveness of using private methods in improving students' reading skills at Madrasah Diniyah TPA/TPQ "HIDAYATUSH SHIBYAN". This research uses a systematic and scientific quantitative approach to explore the relationship between the use of private methods and the ability to read iqra'. This research method is included in the exploratory category, with a survey approach carried out in the field. Data was collected through interviews, observation and documentation. The results of the research show that reading mastery is the main focus in the learning process at Madrasah Diniyah TPA/TPQ "HIDAYATUSH SHIBYAN". Even though there is only one teacher teaching in each class, all students receive equal attention and the material is taught with variety to keep students interested. The application of private methods allows more intense interaction between teachers and students, facilitating better understanding of learning material. However, the success of this method depends on the balance between the number of teachers and students and the availability of sufficient time. This research concludes that learning methods that focus on individual interactions between teachers and students, such as private methods, are effective in improving students' reading abilities and comprehension at Madrasah Diniyah TPA/TPQ "HIDAYATUSH SHIBYAN". The research results provide valuable insights for educational practitioners in improving the quality of learning in non-formal educational institutions and confirm the importance of focusing on reading mastery in the educational process.